UNIQUE PRESENTATION OF NON- HODGKIN’S LYMPHOMA - SUMITHA .R; ABERNA GOVAR (International Journal of Pharma and Bio Sciences, 2013)
Unilateral Tonsillar Enlargement can occur due to infection, chronic inflammation and benign & malignant neoplasms. Squamous cell carcinomas and Lymphomas have been the most commonly associated neoplasms with unilateral tonsillar enlargement.Here we are discussing a case of Unilateral Tonsillar Enlargement with no associated symptoms which was diagnosed as Stage 3 Non- Hodgkin’s Lymphoma by Tonsillar biopsy.